Systematic review of MRI safety literature in relation to radiofrequency thermal injury prevention - Cassandra Baker; Barbara Nugent; David Grainger; Johnathan Hewis; Christina Malamateniou (Journal of Medical Radiation Sciences)
Abstract Introduction Magnetic resonance imaging (MRI) is a rapidly evolving modality, generally considered safe due to lack of ionising radiation. While MRI technology and techniques are improving, many of the safety concerns remain the same as when first established. Patient thermal injuries are the most frequently reported adverse event, accounting for 59% of MRI incidents to the Food and Drug Administration (FDA). Surveys indicate many incidents remain unreported. Patient thermal injuries are preventable and various methods for their mitigation have been published. However, recommendations can be variable, fragmented and confusing. The aim of this systematic review was to synthesise the evidence on MRI safety and associated skin injuries and offer comprehensive recommendations for radiographers to prevent skin thermal injuries. Methods Four journal databases were searched for sources published January 2010–May 2023, presenting information on MRI safety and thermal injuries. Results Of 26,801 articles returned, after careful screening and based on the eligibility criteria, only 79 articles and an additional 19 grey literature sources were included (n = 98). Included studies were examined using thematic analysis to determine if holistic recommendations can be provided to assist in preventing skin burns. This resulted in three simplified recommendations: Remove any electrically conductive items Insulate the patient to prevent any conductive loops or contact with objects Communicate regularly Conclusion By implementing the above recommendations, it is estimated that 97% of skin burns could be prevented. With thermal injuries continuing to impact MRI safety, strategies to prevent skin burns and heating are essential. Assessing individual risks, rather than blanket policies, will help prevent skin thermal injuries occurring, improving patient care.